Improving Students’ Writing Skill in Descriptive Text by Using Outdoor Activity - Sri Suharmi (Register Journal, 2015)
This study is a classroom action research. The general objective of this study is improving students’ writing skill through outdoor activity. While the specific objective of this research are (1) whether or not outdoor activity can increase the students’ writing content of descriptive text of the second year of Mts Sudirman Kopeng  Getasan. (2) it describe whether the outdoor activity can improve  the students’ writing skill in developing paragraph. This classroom action research was conducted at MTs Sudirman Getasan. The procedure of the research consisted of planning, action, observing, and reflection. The observation during the process of English teaching and learning was helped by the collaborator. In this research,  the writer acted as a practitioner. The test was in the form of pre-test and post –test conducted in cycle 1, cycle 2, and cycle 3. The research result were: (1)  using outdoor activity as a method can improve students’ writing skill, its proved with the student’s improvement score. The mean score of the pre-test of the students was 57 (very poor) and the mean score of the post- test 70 (good). The mean of the post-Test is higher than the mean of the pre-Test ( 64.53>56.56), the mean of the post-test in cycle 2  is higher than mean of cycle 1 (70.59>64.53) and the mean of the post –Test cycle 3 is higher than cycle 2 (74.56>70.59). the proven result of the implementation was 75%. (2) The effectiveness of using outdoor activity in improving students’ writing skill is proved from the t-test and t-table in cycle 1 (9.67>2.042) which the score of t-test was higher than the score of t-table and the result of t-test and t-table in cycle 3 (15.11>2.042) also showed that the score of t-table.